Single-incision chronic distal biceps tendon repair with tibialis anterior allograft - Cross, Michael B. (Springer Berlin Heidelberg, 2013)
PURPOSE: Several techniques for chronic distal biceps tendon repair have been reported; however, the literature is sparse. METHODS: Seven male patients who underwent chronic distal biceps tendon reconstruction were retrospectively evaluated. All patients had significant retraction necessitating the use of an allograft for reconstruction. The procedure was done through a single incision using suture anchors and a tibialis anterior allograft. In each case, the graft was first fixed to the radial tuberosity with suture anchors, and then the allograft was sutured to the remnant of the native biceps tendon at 60° of elbow flexion. Patients were evaluated with the Mayo Elbow Performance Score (MEPS), Disabilities of Arm, Shoulder and Hand (DASH) scores and elbow range of motion (ROM). RESULTS: The average time from injury to surgery was 25 (12–56) weeks, and the average follow-up was 16 (minimum 12) months. Average postoperative elbow ROM was as follows: extension 4° (0–12°), flexion 134° (130–140°), pronation 82° (75–85°) and supination 80° (70–85°); average MEPS was 94 (80–100); average DASH score was 6.67 (0–19.8). One patient developed a lateral antebrachial cutaneous neuritis postoperatively that resolved by three months. CONCLUSION: Though many reported techniques for chronic distal biceps tendon repair achieve satisfactory outcomes with limited complications, we present a technique with theoretical advantages of a single incision, use of suture anchors, use of a tibialis anterior allograft and tensioning after attachment of the graft to the radial tuberosity. In a series of complicated patients, early results were good to excellent.